The etiology of oxidative stress in insulin resistance - Hurrle, Samantha (Biomed J, 2017)
Insulin resistance is a prevalent syndrome in developed as well as developing countries. It is the predisposing factor for type 2 diabetes mellitus, the most common end stage development of metabolic syndrome in the United States. Previously, studies investigating type 2 diabetes have focused on beta cell dysfunction in the pancreas and insulin resistance, and developing ways to correct these dysfunctions. However, in recent years, there has been a profound interest in the role that oxidative stress in the peripheral tissues plays to induce insulin resistance. The objective of this review is to focus on the mechanism of oxidative species generation and its direct correlation to insulin resistance, to discuss the role of obesity in the pathophysiology of this phenomenon, and to explore the potential of antioxidants as treatments for metabolic dysfunction.